Jewish philosophical politics in Germany, 1789-1848 - Rose, Sven-Erik (Tauber Institute for the Study of European Jewry series (Unnumbered), 2014)
"Fresh look at how Jewish intellectuals thought about Judaism within a German philosophical tradition"--